111k views
5 votes
Simplify (5 - p2 - 4q) - ( -2 + q - 3p2)
plss hurry!!!!

2 Answers

7 votes

Answer:

2p²−5q+7

Step-by-step explanation:

5−p²−4q−(−2+q−3p²)

Distribute the Negative Sign:

=5−p²−4q+−1(−2+q−3p²)

=5+−p²+−4q+(−1)(−2)+−1q+−1(−3p²)

=5+−p2+−4q+2+−q+3p2

Combine Like Terms:

=5+−p²+−4q+2+−q+3p²

=(−p²+3p²)+(−4q+−q)+(5+2)

=2p²+−5q+7

User JPD
by
5.3k points
6 votes

Answer:

2p^2−5q+7

Step-by-step explanation:

Let's simplify step-by-step.

5−p2−4q−(−2+q−3p2)

Distribute the Negative Sign:

=5−p2−4q+−1(−2+q−3p2)

=5+−p2+−4q+(−1)(−2)+−1q+−1(−3p2)

=5+−p2+−4q+2+−q+3p2

Combine Like Terms:

=5+−p2+−4q+2+−q+3p2

=(−p2+3p2)+(−4q+−q)+(5+2)

=2p2+−5q+7

Answer:

=2p^2−5q+7

User Semisonic
by
5.4k points